1972
DOI: 10.1113/jphysiol.1972.sp010045
|View full text |Cite
|
Sign up to set email alerts
|

Daily changes in foetal urine and relationships with amniotic and allantoic fluid and maternal plasma during the last two months of pregnancy in conscious, unstressed ewes with chronically implanted catheters

Abstract: SUMMARY1. The fluid sacs and bladders of ten foetuses and the allantoic sacs of five foetuses were catheterized between 79 and 96 days gestational age and daily samples were withdrawn until lambs were born naturally at 147 days. Maternal jugular plasma obtained daily allowed the nutritional status of each ewe to be regulated and monitored. All lambs were observed for 7 weeks, and at post-mortem no abnormalities were seen in those operated upon in utero. 6. Changes in urine composition suggested large daily var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
29
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 28 publications
10
29
0
Order By: Relevance
“…The values and patterns of change in fetal urine composition are similar to those of Mellor and Slater [1972]. Changes in amniotic fluid composition parallel changes in urine composition, supporting the view that urine may be a major source of amniotic fluid.…”
Section: Composition Of Fetal Fluidssupporting
confidence: 65%
See 1 more Smart Citation
“…The values and patterns of change in fetal urine composition are similar to those of Mellor and Slater [1972]. Changes in amniotic fluid composition parallel changes in urine composition, supporting the view that urine may be a major source of amniotic fluid.…”
Section: Composition Of Fetal Fluidssupporting
confidence: 65%
“…Although this dose always caused an increase in urine osmolality, in five experiments the flow rate also rose. It is concluded that the ovine fetus has the ability to control its own urine flow and composition, and possibly also amniotic fluid volume and composition.Although the compositions of ovine fetal urine and amniotic fluid have been studied by several groups of workers [Alexander, Nixon, Widdas and Wohlzogen 1958;Mellor and Slater, 1972], little is known of the mechanisms which control the volumes and compositions of these fluids. Urine formation begins at about the third month of fetal life in the human [Vernier and Smith, 1968] and by the third trimester is thought to be an important source of amniotic fluid.…”
mentioning
confidence: 99%
“…In contrast, there was no significant variation in fetal corticosteroids between 09.00 and 24.00 h in ewes fed hourly (Slater & Mellor, 1981). These authors proposed that the rise in fetal plasma corticosteroids induced by feeding may have been due to a fetal ACTH response to the decrease in fetal blood volume which apparently follows maternal feeding (Mellor & Slater, 1973). There are other physiological consequences of feeding, however, such as changes in maternal and fetal plasma concentrations of glucose which could also be important in the stimulation of cortisol secretion in the late-gestation fetal sheep (Jones, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…of urine per day (Alexander, Nixon, Widdas & Wohlzogen, 1958;Rankin, Gresham, Battaglia, Makowski & Meschia, 1972). Foetal urine is essentially lacking in glucose which is present in amniotic fluid; [Na+], [K+] and [Cl-] are lower in foetal urine than in amniotic fluid (Mellor & Slater, 1972). Following urination, then, the composition of the amniotic fluid would be altered.…”
Section: Discussionmentioning
confidence: 99%